Corrigendum to “The Atlantic Forest of South America: Spatiotemporal dynamics of the vegetation and implications for conservation” [Biol. Conserv. 291 (2024) 110499] (Biological Conservation (2024) 291, (S0006320724000600), (10.1016/j.biocon.2024.110499)) - Vancine, Maurício Humberto [UNESP]; Muylaert, Renata L.; Niebuhr, Bernardo Brandão [UNESP]; Oshima, Júlia Emi de Faria; Tonetti, Vinicius [UNESP]; Bernardo, Rodrigo [UNESP]; De Angelo, Carlos; Rosa, Marcos Reis; Grohmann, Carlos Henrique; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2024)
The authors would like to clarify some information related to the results of the analysis. They are presented in the corrections below: 1. We updated the Highlights to: “Since 2005, there has been an increase of 1 Mha in the forest area, partly in new and small fragments (1 ha).” 2. We updated the text presented in Results. Our analyses showed an important gain of ca. 1 Mha in forests between 2005 and 2020. However, not all gains in forest area occurred due to the emergence of new fragments; more than half of that was due to the increase in size of already existing fragments. To make sure all readers correctly understand the results, we have updated the text. Moreover, we now present additional data support the interpretation of our findings. The change is on Page 4, section “3.2. Number of fragments and fragment size distribution”, fifth paragraph. Original: “The temporal dynamics of the landscape from 1986 to 2005 revealed a reduction in the total area of 4.87 Mha of FV (3%) and 5.56 Mha of NV (3.4%) (Table S6). However, between 2005 and 2020, there was an increase of 990,000 ha of FV (0.6%) and a small decrease of 240,000 ha of NV (0.15%). Considering the balance of fragments gained and lost, in the first period there was a sharp drop in the number of fragments for FV (242,000) and NV (227,000), but in the second period there was an increase for FV (385,000) and NV (314,000). Between 1986 and 2005, the average size of lost FV and NV fragments (1.2 to 1.35 ha) was greater than the size of restored fragments (1.08 to 1.14 ha); between 2005 and 2020, this pattern reversed, with the average size of fragments lost being smaller (0.94 to 0.97 ha) than that of fragments gained (1.03 to 1.08 ha).” This is now replaced by: “The temporal dynamics of the landscape from 1986 to 2005 revealed a reduction in the total area of 4.87 Mha of FV (3%) and 5.57 Mha of NV (3.4%). In contrast, between 2005 and 2020, there was an increase of 981,000 ha of FV (0.6%) and a small decrease of 244,000 ha of NV (0.15%). Of the total FV gain in the period 2005-2020, 541,000 ha (0.33%) were gained by expanding the area of existing fragments, and 440,000 ha (0.27%) in new fragments; for NV, there was a loss of 600,000 ha (0.37%) of existing fragments and a gain of 356,000 ha (0.22%) in new fragments. Considering the balance of fragments gained and lost, in the first period there was a sharp drop in the number of fragments for FV (243,000) and NV (227,000), but in the second period there was an increase for FV (386,000) and NV (314,000). Between 1986 and 2005, the average size of fragments lost (1.33 ha for FV and 1.2 ha for NV) was greater than the size of fragments gained (1.12 ha for FV and 1.08 ha for NV). Between 2005 and 2020, this pattern reversed, with the average size of fragments lost being smaller (0.96 ha for FV and 0.94 ha for NV) than fragments gained (1.06 ha for FV and 1.03 ha for NV) (Table S6).” 3. We updated the order of the plots in Fig. 8 (so that figures a and c come in the first column and are presented before plots b and d in the second column).4. We updated Table S6 in Supplementary material, now presenting gained area values for previously existing fragments.The authors would like to apologise for any inconvenience caused. [Formula presented]